Patient Safety and Risk Management 2017
DOI: 10.1136/ejhpharm-2017-000640.564
|View full text |Cite
|
Sign up to set email alerts
|

PS-058 Evaluation of clinical pharmacists’ interventions in a cardiology department

Abstract: BackgroundPrevious studies have reported that clinical pharmacists improve medication safety. A clinical pharmacy team (1 senior pharmacist, 1 junior pharmacist, 7 student pharmacists) was deployed in cardiology units (79 beds) to develop medication reconciliation (MR), identify medication errors (ME) and optimise patients’ pharmacotherapy.PurposeThe aim of this study was to describe and analyse pharmacists’ interventions in cardiology units over 9 month and to evaluate their impact on the management of cardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Most of these interventions were accepted by the medical team (91.5%), the result of which is similar to what has been reported in other studies. 10,11 One study that was conducted between 2002 and 2003 in our organization looked at the impact of clinical pharmacists in a cardiac surgery intensive care unit and found that the acceptance rate of clinical pharmacists' interventions during the study period was 94.3%. 10 Other information collected in our study shows the extent of clinical pharmacists' involvement in, contribution to, and development of a comprehensive patient care plan.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these interventions were accepted by the medical team (91.5%), the result of which is similar to what has been reported in other studies. 10,11 One study that was conducted between 2002 and 2003 in our organization looked at the impact of clinical pharmacists in a cardiac surgery intensive care unit and found that the acceptance rate of clinical pharmacists' interventions during the study period was 94.3%. 10 Other information collected in our study shows the extent of clinical pharmacists' involvement in, contribution to, and development of a comprehensive patient care plan.…”
Section: Discussionmentioning
confidence: 99%